Antitumor Effect Induced by Protozoa and Helminth Infections: Current Trends and Future Perspectives. - García López, I. (2024)
Cancer is one of the main causes of morbidity and mortality worldwide. Currently, surgery, radiotherapy, and systemic therapy are common treatments for different types of human cancer. However, these treatments are often ineffective; thus, the development of novel and cost-effective therapeutic strategies is necessary. In recent years, the antitumor effect of infection by some protozoa and helminths has been reported but the molecular mechanism is not completely clear. The in vitro and in vivo studies have indicated the presence of effector molecules capable of activating the acute inflammatory responses against the tumor, mediating the antiangiogenic response, and inducing modulation of the microenvironment to trigger either suppression or progression of tumor development. In this chapter, the antitumor mechanisms induced by parasitic infection will be reviewed.